Plasma C-reactive protein and selected nutritional indices in elective caesarean section (2009)
Context: Caesarean Section (CS) is a major surgical procedure, often performed when a vaginal delivery is considered unsafe. Objective: This study was carried out to understand the interaction between acute phase proteins and nutritional factors consequent to caesarean section. The knowledge of this interaction is important for successful management of these patients. Methods: Plasma samples from fifty (50) pregnant women booked for elective caesarean section in Ibadan, Nigeria were collected on the day preceding surgery, one day and four days post-surgery to determine the levels of CRP, vitamin C, PCV, Total protein, albumin and globulin (Glb) levels. Results: The mean age of the patients studied was 32.29 + 3.66 years, range; 24 39 years. Significant elevations were observed in the levels of TP, Glb and CRP one day post-surgery (1DPS) compared with baseline (BS) (7.36 + 1.46) vs 6.56±1.30, (4.68 + 1.33) vs 2.70±1.51, (111.43 + 68.89) vs 6.00 ± 13.27 respectively, while albumin reduced significantly (2.68 + 1.08) vs 3.87±0 .63. Similar changes were observed on day 4. There was no significant change in the levels of Vitamin C. Conclusion: One of the positive predictive indicators of good outcome after caesarean delivery is adequate nutrition.